Wage shares and demand regimes in Central America: An empirical analysis for Costa Rica, El Salvador, Honduras, Nicaragua, and Panama, 1970-2016 - Valeria Jiménez (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2020)
This paper analyzes the relationship between functional income distribution aggregate demand and economic growth in five Central American countries; Costa Rica, El Salvador, Honduras, Nicaragua, and Panama for the period 1970-2016. It estimates the effects of a change in the wage share on aggregate demand based on a post-Kaleckian model, which allows for either profit- or wage-led demand. The results show that the domestic demand is wage-led in the five countries. The same applies for total demand with the exception of Panama, whose domestically wage-led demand turns profit-led when including the effect of distribution on net exports. Finally, it is argued that there is room for a wage-led recovery in Central America.
Keywords: E12; E22; E23; E25; E61; F41; 330; distribution; aggregate demand; wage share; demand regimes; consumption; investment; net exports; developing countries; Central America